Leveraging ChatGPT to address patient queries on fever of unknown origin: opportunities and limitations - Gundala, Prajwal (International Journal of Research in Medical Sciences, 2026)
Fever of unknown origin (FUO) remains one of the most intriguing and diagnostically challenging syndromes in internal medicine. The term FUO itself implies a passive/negative approach to diagnosis, suggesting a state of uncertainty that may perpetuate medical inertia. FUO is defined as a temperature ≥38.3°C (101°F) on several occasions for at least three weeks without an established diagnosis despite appropriate evaluation.1 In resource-limited settings an active and pragmatic approach is essential to expedite diagnosis and mitigate burden of undiagnosed fever cases.2 In contrast, access to large language models like ChatGPT has been increasing over past few years.3 Developed by OpenAI, ChatGPT is a large language model capable of giving human-like answers to queries related to health by compiling information from medical literature.5 Patients are increasingly using AI to clarify medical terminologies and physicians’ advice.3 Patients suffering from FUO search online for explanations of symptoms and investigations, where information may be incomplete or misleading.